Peningkatan Kompetensi Guru TPQ Dan MDT Se-Kota Padang Melalui Pelatihan Al-Qur’an Yang Efektif - Warlan Sukandar (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This community service activity aims to improve the competence of TPQ (Al-Qur'an Education Park) and MDT (Madrasah Diniyah Takmiliyah) teachers throughout Padang City in teaching the Qur'an effectively. The background to this activity is the fact that many TPQ and MDT teachers have not received adequate pedagogical training. As a result, the Qur'an learning they conduct tends to be monotonous and less interesting for children, thus reducing students' interest and understanding of the Qur'an. This training was conducted over two days with a participatory approach involving 100 participants from various TPQ and MDT institutions in Padang City. The material presented in the training included active learning methods that can activate student participation in class, the use of simple, easy-to-implement teaching media, and Islamic character building strategies that aim to shape noble morals in students. The training results showed a significant increase in the participants' teaching knowledge and skills, where they better understand more interesting and interactive teaching methods. In addition, participants' motivation to continue improving the quality of their teaching also increased. One of the important achievements of this training was the formation of a network among TPQ and MDT teachers that can serve as a forum for sharing good practices in teaching the Quran, so that teachers can learn from each other and improve the quality of their teaching together. The conclusion of this activity is that training designed with the right approach can have a real impact on improving the quality of Quran teaching in TPQ and MDT. Therefore, this activity provides recommendations to TPQ-MDT managers, the community, and the government to continue supporting the development of teacher competencies on an ongoing basis. In addition, it is recommended that further research further examine the impact of learning on student development in terms of knowledge and character.